The questions and features of world-formation-terminology in arabic language - Aбуов, Б. У.; Мустaфaевa, A. A. (Journal of Oriental Studies, 2017)
In this article I have looked through the newspaper “Al-Ahram” the years 2012 till 2013. They are the forms of types of using political terms their way, of lexical, morphological structures in general these articles research language study theory.